Ecological and human health risk assessment. (9th July 2020) - Choudri, B. S.; Al‐Nasiri, Noura; Charabi, Yassine; Al‐Awadhi, Talal
Abstract: The literature review presented in this paper includes the ecological and human health risk assessment in the form of receptors in the environment. The main objective of this review to highlight a summary of the many studies undertaken in the year 2019. The first part of the review covers the papers published on the health risk assessment related to human and ecological health. This article focuses on methods and tools utilized for the analysis of scientific studies and the data. The review provides main issues such as interpretation of data, uncertainty, and policies related to the management of risks. The ecological and human health risk assessment is divided into two main sections. Each of these sections presents in broad the risk assessment process namely pollution studies, remediation, and tools required for the management of natural resources and the environment.